Evaluation of Implant Stability and Marginal Bone Level for Immediately Placed Dental Implants in Fresh Extraction Sockets Augmented with Phase-pure Beta-tricalcium Phosphate - Ali Ghaith Ahmed (Journal of Global Pharma Technology, 2016)
Objectives: The aims of this study were to evaluate dental implant stability and marginal bone level after immediate implant placement with simultaneous grafting of the gap with alloplastic material. Materials and methods: This prospective study included patients who required an extraction of hopeless teeth and subsequent immediate implant placement at a non-molar site, Full thickness mucoperiosteal flap was elevated and the buccal plates were intact in all cases. Following dental implant placement the primary stability was measured with Periotest. The gap was filled with alloplastic grafting material (Easy graft) and wound closure, then a cone beam computed tomography (CBCT) was taken. 6 months later, a second CBCT was performed and a comparison between them was made for the evaluation of marginal bone level change. Results: Twenty patients with 31 dental implants were enrolled in this study. The difference between base line and 6 months for buccal cortical plate level , palatal/lingual cortical plate level were 0.93 ± 1.15 mm , 0.57 ± 0.94 mm respectively with a highly significant difference (P=0.007) between buccal and palatal cortical plate. For primary implant stability the mean was 4.98 ± 4.26 PTV, while secondary stability was 1.36 ± 2.96 PTV with a highly significant difference (P=0.001) between primary and secondary stability. Conclusion: Good primary implant stability was achieved even in the presence of gap and the stability was adequate to attain good secondary stability after 6 months. Gaps more than 2 mm were successfully managed with rapid setting Easy graft with promising influence on stability and marginal bone level. Implant length inversely affected PTV. Bone resorptions of the cortical plate occurred more labailly/ buccally than palatally/ lingually and maximum resorption happened in the canine region.